Analysis of External Factors that Affect Non-Performing Loans to Bank Customers in Boyolali - Erna Febrianti; Astuning Saharsini (Journal of Business, Management, & Accounting, 2022)
This study aims to determine the external factors of the customer, namely the character of the debtor, managerial ability, business conditions, the use of credit that is not good for non-performing loans at commercial banks in Boyolali. The method used is by using a questionnaire to 70 respondents. Purposive Sampling was done by purposive sampling method. Data were analyzed using Multiple Linear Regression Analysis with the help of the Statistical Package for the Social Sciences (SPSS.Ver 19) program. The results of data analysis research show that external factors on the character of the debtor have no significant effect on non-performing loans, managerial ability has a negative and significant effect on non-performing loans, business conditions have a positive and significant effect on problem loans, the use of bad credit has a positive and significant effect on non-performing loans.